Credit Guarantee the National Economic Recovery Program (PEN) for MSMEs: A Case Study of MSMEs for Bank Pembangunan Daerah DIY - Muhammad Safar Nasir; Mahrus Lutfi A.K.; Nur Andriyani; Ana Rahamawati Wibowo; Yolanda Oktaviani (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2022)
In recent months the world has been shocked by a deadly virus, namely Coronavirus Disease 2019 or better known as the COVID-19 virus, which causes a health crisis and an economic crisis. National Economic Recovery or PEN is one of the policies to improve the country's economic conditions due to the COVID-19 pandemic which has a systemic impact. The impact affects almost all sectors, including the Micro, Small and Medium Enterprises sector. This study aims to analyze credit guarantees on MSME income in Daerah Istimewa Yogyakarta (DIY). This study uses a qualitative descriptive method, with UMKM recipients of PEN program assistance through Bank BPD DIY as respondents. The collection technique was through interviews and questionnaires with a total sample of 30 respondents and selected based on the purposive sampling method. The rate of return and the questionnaire that can be processed is 100%. From the results of interviews that have been carried out, it was concluded that in general new working capital credit guarantees help entrepreneurs in recovering MSME businesses due to being affected by COVID-19. The results of this study are in accordance with the Government's target that the assistance in credit guarantees helps micro-enterprises to increase their business income.